HF Test Current Injection Based Self-Sensing Control of PMSM for Low and Zero Speed Range Using Two-Degree-of-Freedom Current Control. - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using Two-Degree-of-Freedom current control one can overcome the bandwidth limitations which made test current injection unattractive during the last 20 years. The Two-Degree-of-Freedom control scheme consists of a model based dynamic feed forward control to set the reference response and model reference tracking controllers providing disturbance rejection and the position error signals for self-sensing control. Since Two-Degree-of-Freedom control is a model based control scheme the compensation for secondary saliencies is inherently included in the pre-control. It is shown analytically that in case of test current instead of voltage injection just the precise knowledge of the current and position dependent inductance mqd HF is needed in case of inductance saliency based sensorless control. The effectiveness of the proposed method is proven by experimental results. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.hftest
Keywords: permanent magnet motors; saliency; sensorless control; test current injection